Encapsulation of Asexual Embryos Towards Production of Artificial Seeds in Eggplant (Solanum melongena L.) (Bangladesh Journal of Genetics and Biotechnology, 2009)
Keywords: Somatic embryo; artificial seed; sodium alginate; germination; eggplant Bangladesh j. genet. biotechnol. 7 (1&2): 87-90, 2006 (June & December)